Forward guidance and expectation formation: A narrative approach - Christopher S. Sutherland (Bank of Canada, 2020)
How forward guidance influences expectations is not yet fully understood. To study this issue, I construct central bank data that includes forward guidance and its attributes, central bank projections, and quantitative easing, which I combine with survey data. I find that, in response to a change in forward guidance, forecasters revise their interest rate forecasts in the intended direction by five basis points on average. The effect is not attributable to central bank information effects. Instead, when forming rate expectations, forecasters place full weight on their own inflation and growth forecasts and zero weight on those of the central bank.
Keywords: D83; D84; E37; E52; E58; 330; Central bank research; Monetary policy; Monetary policy communications; Transmission of monetary policy